2022
DOI: 10.1093/jbi/wbac041
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Early Detection: Evidence From Modern International Mammography Service Screening Programs

Abstract: Research from randomized controlled trials initiated up to 60 years ago consistently confirms that regular screening with mammography significantly reduces breast cancer mortality. Despite this success, there is ongoing debate regarding the efficacy of screening, which is confounded by technologic advances and concerns about cost, overdiagnosis, overtreatment, and equitable care of diverse patient populations. More recent screening research, designed to quell the debates, derives data from variable study desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Eby's research in 2022 also stated that the results of observational studies conducted in Europe, Canada, Australia, New Zealand, and Korea showed that the implementation of early breast cancer detection programs significantly reduced the morbidity of advanced-stage cancer and reduced the need for chemotherapy. Moreover, radiation therapy extends patients' lives, reducing the risk of breast cancer death (Eby et al, 2022).…”
Section: Program Achievementmentioning
confidence: 99%
“…Eby's research in 2022 also stated that the results of observational studies conducted in Europe, Canada, Australia, New Zealand, and Korea showed that the implementation of early breast cancer detection programs significantly reduced the morbidity of advanced-stage cancer and reduced the need for chemotherapy. Moreover, radiation therapy extends patients' lives, reducing the risk of breast cancer death (Eby et al, 2022).…”
Section: Program Achievementmentioning
confidence: 99%